Is biblical womanhood obsolete? : Exploring new ways to teach biblical womanhood - Stoddard, Eowyn (Covenant Theological Seminary, 2024)
1 online resource (x, 194 leaves) ; Abstract; D. Min. Covenant Theological Seminary, 2024 ; Bibliographical references (leaves 183-194)